Jak se děje ájurvéda - Wolfová, Alžběta (Lidé města, 2015)
Despite the favourite approach of the social sciences, I do not intend to discuss Ayurveda in terms of the distance between its traditional and modern (globalised) v ersion. For an almost complete absence of standardisation of Ayurveda in the Euro-American regions, I have assumed a high plurality of its forms. I have drawn upon ethnographic research based in an Ayurvedic institution in the Czech Republic, which serves as a school for future Ayurvedic practitioners, as a consultation and healthcare centre, as a community centre, and as a shop with Ayurvedic medicines. The aim of this paper is to show how a specific Ayurveda “is done” in the local socialnatural environment. To reach this point, I discuss the main actors and practices involved in the process of the enactment of Ayurveda. Inspired by several Latourian thoughts, I have attempted to work symmetrically – to pay the same attention to the material, the social, and the discursive aspect of this phenomenon. In this case, Ayurveda has been formed by teaching, studying, recovering and expanding through its community, by organising a daily regime in the terms of food, yoga and breathing exercises, and also by defining its medicines through legislative processes. Crucial roles in this process are played by the Teacher, the Doctrine, and the Space of the Ayurveda Institution itself – its schedule and regulations, its community –, by the food, physical exercises and medicines.